The Water-Drinking Test Revisited: An Analysis of Test Results in Subjects with Glaucoma. (19th May 2018) - Razeghinejad, M. Reza; Tajbakhsh, Zahra; Nowroozzadeh, M. Hossein; Havens, Shane J.; Ghate, Deepta; Gulati, Vikas
ABSTRACT: Purpose : The Water-Drinking Test (WDT) has been shown to predict the diurnal IOP change. This study evaluates the factors that may affect the WDT results. Methods : This study was conducted on 203 glaucoma patients who had undergone trabeculectomy (53) or tube surgery (31), or had a medically controlled open-angle (82) or closed-angle (37) glaucoma. IOP was measured at baseline and then every 15 minutes over a one-hour period after drinking water. The main outcome measures were IOP change (increase in IOP from baseline) at all measurement time points, IOP peak (highest IOP after drinking water), IOP fluctuation (difference between IOP peak and baseline), and assessing the association of these IOPs with a patient's demographic and management modalities. Results : The mean age of the participants was 54±18 years, and 113 (56%) were male. Female patients showed greater IOP fluctuation than males (7.28 vs. 5.92 mm Hg; P =0.016), and a greater IOP peak (22.7 vs. 20.1 mm Hg; P =0.001). The observed associations between gender and IOP changes were only significant in <50 years. IOP at 60 minutes was greater in tube than trabeculectomy (5.6 vs. 3.1 mm Hg; P =0.007). The number of topical medications showed a direct independent association with IOP changes ( P <0.001). Compared to other classes of topical medications, latanoprost showed lower WDT-IOP profile ( P =0.0003). Conclusions : WDT-IOP change was diminished in subjects on latanoprost, and was greater in females <50 years, and those on greater number of medications.